ANALISIS KONTRIBUSI PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA PONTIANAK - B01111001, Dionisia Indah Rastika Sari (Jurnal Pembangunan dan Pemerataan, 2016)
The title of this research is analysis contribution of hotel and restaurant tax to the increase of regional income in Pontianak City. The aims of this study is to determine the contribution of hotel and restaurant tax to regional income in Pontianak City and determine how much the influence of hotel and restaurant tax to regional income in Pontianak City. This research uses descriptive method with quantitative approach usingcontribution analysis, multiple linear regression model, the classic assumption test, as well as statistical analysis tools that is test of determination (R2), F test and t test to test the hypothesis of whether the hotel and restaurant tax effects towards regional income. The result of this research using contribution analysis showed that the hotel tax on 2000-2013 give 7,46% and restaurant tax give 11,30% to the regional income. And then when using multiple linear regression model, hotel tax positively affect by 0,336 but not significant and the restaurant tax positively affect by 4,949 and significant to the increase of regional income in Pontianak City. The coefficient of determination value by 0,939 which means that major influence exerted by hotel and restaurant tax to the increase of regional income in Pontianak City by 93,9%, while the remaining 6,1% are affected by other factors. Keywords: Regional Income, Hotel Tax, Restaurant Tax